2012
DOI: 10.1111/j.1600-0706.2012.020215.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pace of life and immune responses in wild rodents

Abstract: Life histories of animals tend to vary along a slow to fast continuum. Those with fast life histories have shorter life spans, faster development, and higher reproductive rates relative to animals with slower life histories. These differences in life histories have been linked to differences in investment in immunological defenses. Animals with faster life histories are predicted to invest relatively more in innate immune responses, which include rapidly‐deployed, non‐specific defenses against a broad spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
129
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(136 citation statements)
references
References 59 publications
(90 reference statements)
7
129
0
Order By: Relevance
“…Given these characteristics, it has been hypothesized that organisms with fast pace-of-life strategies-characterized by rapid growth, early maturation, and high reproductive rate but a short life span-should rely more on innate immune defenses, whereas slow-living organisms-characterized by a long life span but slow growth, delayed maturation, and a lower reproductive rate-should rely more on adaptive immune defenses (Lee 2006). Despite the intuitive appeal of this hypothesis, few studies to date have tested its predictions, and support remains mixed (Lee et al 2008;Sparkman and Palacios 2009;Cutrera et al 2010;Previtali et al 2012). …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given these characteristics, it has been hypothesized that organisms with fast pace-of-life strategies-characterized by rapid growth, early maturation, and high reproductive rate but a short life span-should rely more on innate immune defenses, whereas slow-living organisms-characterized by a long life span but slow growth, delayed maturation, and a lower reproductive rate-should rely more on adaptive immune defenses (Lee 2006). Despite the intuitive appeal of this hypothesis, few studies to date have tested its predictions, and support remains mixed (Lee et al 2008;Sparkman and Palacios 2009;Cutrera et al 2010;Previtali et al 2012). …”
Section: Introductionmentioning
confidence: 97%
“…Unlike many innate immune measures, most measures of acquired immunity routinely used by ecoimmunologists often necessitate two captures (e.g., in vivo antibody response to a challenge and delayedtype hypersensitivity response). Thus, in cases where recapture of individuals in the field is difficult, acquired immune measures have been obtained mainly from animals brought into captivity (e.g., Martin et al 2006;Cutrera et al 2010;Previtali et al 2012). An alternative approach is to use measures of acquired immunity that do not require repeated captures in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent research suggests that immunological tolerance, and hence high host competence, tends to characterize the species that are intrinsically more likely to persist when diversity declines (62). Related research has indicated that hosts with a high intrinsic rate of increase are both more ecologically resilient and reservoir competent (58).…”
Section: Highlights Of the Recent Literaturementioning
confidence: 99%
“…Discussions about infection-induced changes in host fitness typically consider four general theoretical constructs: HDT, pathogen activity, limiting resource economics, and host fitness (e.g., De Leo and Dobson 1996;Roy and Kirchner 2000;Stowe et al 2000;Dobson 2004;Cable et al 2007;Miller et al 2007;Cronin et al 2010b;Johnson et al 2012;Previtali et al 2012;Huang et al 2013). HDT is the primary developmental process that influences and causes correlations among functional traits, namely, physiological, structural, behavioral, and life-history traits.…”
Section: Mapping Theoretical Space: Development Of the Semmmentioning
confidence: 99%